Exploring Intercultural Communicative Competence of EFL Higher Education Students: A Communal Perspective - Syam, Anugerah Febrian; Nurhikmah, Andi; AP, Sumrah (Tamaddun Life, 2023)
The purpose of this study is to explore EFL higher education students’ intercultural communicative competence in community interactions based on communal perspectives. The study will employ a qualitative approach using two types of interviews: individual (a face-to-face meeting with one community member) and small group (videoconferencing with two or three members as the representation of the student’s community). Six-phase guide of thematic analysis was employed in this study. The study reveals that the message content and message relationship are displayed as important elements in community interaction. In practicing intercultural communicative competence in the community, EFL students portrayed open-mindedness, self-awareness, and nonverbal communication skills as the key characteristics of effective communication. Furthermore, the emergence of misunderstanding in community interaction is undeniably linked to speaker-related, interlocutor-related, and participant-related trigger. Therefore, EFL students addressed the use of language and the practice of tolerance to incorporate intercultural aspects in community interaction.